A Local Counter-Discourse against National Education Problems: Postcolonial Reading of Andrea Hirata’s Laskar Pelangi - Andreas Akun (K@ta: A Biannual Publication on the Study of Language and Literature, 2010)
This study aims at exploring postcolonial themes raised by Andrea Hirata’s Laskar Pelangi (Rainbow Warriors). Specifically, it will reveal the characteristics of hybridity found in the novel that prove this literary work may be categorized as postcolonial writing despite the fact that western or white colonialism has no impact or trace at all in the novel. Furthermore, the study will prove that this national novel with its very local issues is a counter discourse, a subversive tool for the writer to criticize the domination of certain groups upon their own marginal fellows. Education, as a global issue, is one Indonesian national and typical ironic problem teased through local culture and even mysticism in this novel.